Synergieeffekte zwischen ziviler und militärischer Forschung klug nutzen - Irene Bertschek; Guido Bünstorf; Uwe Cantner; Carolin Häussler; Christoph M. Schmidt; Friederike Welter; Helge Dauchert; Tilman Requate (Wirtschaftsdienst, 2024)
– To synergise civil and military research, their separation should be abandoned and the so-called 'civil clauses' still enshrined in the statutes of many German universities should be reconsidered. Together with its European partners, the German government should establish joint development and procurement processes for the military. Key technologies must be systematically identified and promoted in order to avoid unilateral dependencies in these technology areas that could weaken military security. In order to counter the lack of skilled personnel, the Bundeswehr should train soldiers in such a way that they can use the knowledge they have acquired during their military service in civilian life.
Keywords: O31; O32; O38; 330